Electroencephalogram (EEG) assessment of brain activity before and after electrical stunning in the Nile crocodile (Crocodylus niloticus) - Swan, Gerry E. (University of Pretoria, 2020)
Dissertation (MSc (Veterinary Sciences))--Univeristy of Pretoria, 2019.